SIMULATION OF ARRAYED CURRENT TURBINE DEPLOYMENT FOR OPTIMIZATION OF TIDAL KINETIC ENERGY CONVERSION IN ALAS STRAIT - Lanata Sosrodjojo, Thexon
Tidal currents are one of the most promising renewable energy sources due to their predictable availability. Additionally, the conversion of kinetic energy (current) into electricity has been widely developed and is relatively easier compared to the conversion of potential energy. This energy conversion is achieved using a specific arrangement of current turbines designed to optimize energy production. In this study, the arrangement of turbines and estimation of the most optimal energy production in the Alas Strait were determined using numerical model simulations. The model used is OpenTidalFarm, which employs shallow water equations with solutions obtained using the adjoint method to achieve the objectives of this research. Optimization of 67 turbines in the narrowest part of the Alas Strait near the coast of Sumbawa Island showed that, out of 100 iterations of optimization, power production increased by 4.2%. The power generated with the theoretical turbines before optimization, with an alternating arrangement, was 572.683 watts, which increased to 596.919 watts after optimization.